GPI-anchored diphtheria toxin receptor allows membrane translocation of the toxin without detectable ion channel activity. - Lanzrein, M (1996)
We have investigated the role of the transmembrane and cytoplasmic domains of the diphtheria toxin (DT) receptor [heparin-binding epidermal growth factor (HB-EGF) precursor] in the intoxication pathway. Two mutants were constructed in which these domains were replaced by either a 37 amino acid sequence signalling membrane attachment via a glycosylphosphatidylinositol (GPI) anchor (DTR-GPI) or by the transmembrane and cytoplasmic domains of the human EGF receptor (DTR-EGFR). Similar amounts of DTA fragment were translocated through the plasma membrane of NIH 3T3 cells transfected with the wild-type receptor (DTR), DTR-GPI and DTR-EGFR, but translocation was about six times less efficient in the case of DTR-GPI and DTR-EGFR when taking into account the number of receptors expressed. Interestingly, DT-induced 22Na+ influx was weak in DTR-EGFR cells and not detectable in DTR-GPI cells. Whole cell patch-clamp analysis showed the DT at low pH induced depolarization and decreased input resistance in DTR cells (and to a lesser extent also in DTR-EGFR cells) but not in DTR-GPI cells. These results suggest that the transmembrane and cytoplasmic part of the receptor might be involved in channel activity and that translocation of the A fragment is independent of toxin-induced cation channel activity.